2011
DOI: 10.5032/jae.2011.04175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inquiry–based Agriscience Instruction on Student Achievement

Abstract: Testing to build research-based evidence to support teaching methodologies that promote student learning has become increasingly important in a standards-based educational system in the United States. One challenge is the lack of studies that support specific methodologies so teachers and administers can make professional development and curricular decisions. This quasi-experimental study investigated the effect of two teaching methods on student content knowledge achievement. Inquiry-based instruction was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…Students taught through IBI scored significantly higher on content knowledge exams and scientific reasoning (Thoron & Myers, 2011). This study found a moderate relationship between the method used and the scientific reasoning score.…”
Section: Discussion/implicationsmentioning
confidence: 61%
See 1 more Smart Citation
“…Students taught through IBI scored significantly higher on content knowledge exams and scientific reasoning (Thoron & Myers, 2011). This study found a moderate relationship between the method used and the scientific reasoning score.…”
Section: Discussion/implicationsmentioning
confidence: 61%
“…Means and Voss (1996) stated that reasoning skills and content knowledge are related. As a larger part of this study Thoron and Myers (2011) found students, taught through inquiry-based instruction, scored significantly higher on content knowledge assessments when compared to the subject matter approach. Current teaching methods are not satisfying the needs of individuals entering careers in agriculture, attending major universities, or pursuing other postsecondary education endeavors (NRC, 1998).…”
Section: Effects Of Inquiry-based Agriscience Instruction On Student mentioning
confidence: 99%
“…Moving to Priority 5 of the NRA, "Efficient and Effective Agricultural Education Programs", this notion has underscored the need for advancing agricultural education into a model that emphasizes pragmatic, high-quality, and academically-rigorous curricula. As inquiry-based learning is designed to create relevant and problem-based learning environments (Parr & Edwards, 2004;Thoron & Myers, 2011), the creation and sustainment of high-quality SBAE through this teaching and learning theory is well-supported.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In order to help further enhance students' interests in various content areas, many educators have incorporated the use of inquiry-based learning into their curricula. As supported by educational philosopher John Dewey (1910, as cited in Thoron & Myers, 2011), inquiry-based learning aids in students' processes of discovery about selected topics, particularly those of interest to individual students. As a result, higher-order thinking skills (HOTS) and more cognitively-rooted ideas are more apt to occur (Thoron & Myers, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation